Development of a three-dimensional prognostic score for patients with symptomatic peripheral artery disease: PAD3D score. (25th November 2020) - Dopheide, J.F; Adam, L; Gahl, B; Papac, L; Kaspar, M; Baumgartner, I; Drexel, H
Abstract: Background: Peripheral artery disease (PAD) is a high-risk condition for cardiovascular Events, but no individual prognosis assessment exists. Objectives: We aimed to establish an individual, clinically useful risk score based on the combined predictive value for mortality of (i) age, (ii) severity of PAD, and (iii) extent of atherosclerosis (PAD3D). Methods: 1310 patients with symptomatic PAD underwent follow-up for a mean of 50±26 months. We randomly subdivided the cohort into test and validation cohort. All-cause and cardiovascular mortality were prospectively analysed for the t PAD3D score and in combination with classical risk factors (PADRF). Results: For test and validation cohort (n=655), all-cause and cardiovascular mortality was precisely predicted (both p<0.001) by the PAD3D score (Fig. 1 A+B). The additional inclusion of classical risk factors did not increase discrimination (Fig 1 C+D) compared to PAD3D score, as AU-ROCs were similar for both scores at 12 and 24 months (Fig. 2). Thus, the addition of classical risk factors did not further improve the prognostic value. The PAD3D score provides a risk gradient of a 4.5-fold increase in all-cause and cardiovascular mortality. Conclusions: We established a score for precise prediction of all-cause and cardiovascular mortality. The PAD3D score promises to allow for personalized goals in risk intervention. Funding Acknowledgement: Type of funding source: None